The relation between local structural distortion and the low-temperature magnetic anomaly in Fe7S8. (1st October 2018) - Koulialias, D; Canévet, E; Charilaou, M; Weidler, P G; Löffler, J F; Gehring, A U
Abstract: Structural defects on an atomic level can crucially impact the magnetic properties of a material. We study this phenomenon by means of magnetometry and powder neutron diffraction on a stoichiometric, monoclinic pyrrhotite (Fe7 S8 ), which is a classic omission structure with a magnetic anomaly at about 30 K. The initial structural distortion of the pyrrhotite at 300 K caused by the vacancy arrangement decreases upon cooling, and simultaneous to the magnetic anomaly the anisotropic contraction of the unit cell homogenizes the covalency of the Fe–Fe bonds with lengths less than 3.0 Å and the Fe–S–Fe bond angles. These changes on the atomic level affect the spin–orbit coupling and the super-exchange interactions in Fe7 S8, and trigger the low-temperature magnetic anomaly within a crystallographically stable system.